A Strange Recursion

This is a really nice recursion I wanted to share.

\begin{cases} a_0 = 1 \\ a_{n+1} = 2a_n +\sqrt{3a_n^2 - 2} \end{cases}

We have to find the general formula for the nth term of the succession.

We have:

(a_{n+1} - 2a_n)^2 = 3a_n^2-2

Also:

(a_{n} - 2a_{n-1})^2 = 3a_{n-1}^2-2

By subtracting the two expressions and simplifying we get:

a_{n+1}^2-a_{n-1}^2 -4a_n(a_{n+1}-a_{n-1}) = 0

Now, since a_n > a_{n-1} we can further simplify to get the final form:

a_{n+1} = 4a_n - a_{n-1}

By solving the recursion’s equation we can find the nth term of the sequence.

t^2-4t+1 = 0

Its solutions are 2+\sqrt{3}, 2-\sqrt{3} .

Now by solving the following system we can find constants x and y such that a_n = x(2+\sqrt{3})^n + y(2-\sqrt{3})^n .

\begin{cases} x + y = 1 \\ (2+\sqrt{3})x + (2-\sqrt{3})y = 3 \end{cases}

We find

\begin{cases} x = \frac{1+\sqrt{3}}{2\sqrt{3}} \\ y = \frac{\sqrt{3}-1}{2\sqrt{3}} \end{cases}

So the nth term equals

a_n = \frac{1}{2\sqrt{3}}[(1+\sqrt{3})(2+\sqrt{3})^n + (\sqrt{3}-1)(2-\sqrt{3})^n]

Or

a_n = \frac{1}{\sqrt{3}}[(\frac{1+\sqrt{3}}{2})^{2n+1} - (\frac{1-\sqrt{3}}{2})^{2n+1}]

And the problem is solved.

Scroll to top